Pengaruh Sustainability Performance, Profitability, dan DER Terhadap Keputusan Investasi pada Perusahaan Tambang yang Terdaftar di BEI - Hanisa, Layla; Priyawan, Sunu (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study was conducted to empirically examine the relationship between sustainability performance, profitability, and debt-to-equity ratio with investment decisions in the Indonesian mining sector. Utilizing secondary data—including annual reports and sustainability reports of mining companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024—this study adopts a descriptive quantitative approach. The sample used consisted of 10 companies, determined through purposive sampling from a total population of 101 companies. The results of multiple linear regression analysis using SPSS 25 showed that individually (partially), only sustainability performance significantly affects investment decisions. However, when tested together (simultaneously), the three independent variables collectively exert a significant influence on investment decisions.